The potential of microalgae meal as an ingredient in the diets of early juvenile Pacific white shrimp, Litopenaeus vannamei - Abdul Basri, Najamuddin; Muhamad Shaled, Sitti Raehanah; Matanjun, Patricia; Mohammad Noor, Normawaty (Springer Netherlands, 2014)
This study evaluated the potential of green water meal (GWM) as an ingredient in the diets for early juvenile Pacific white shrimp, Litopenaeus vannamei. Five isonitrogenous and isolipidic diets were formulated with 0 % (control diet), 10, 20, 30, and 40 % (GWM0, GWM10, GWM20, GWM30, and GWM40, respectively) of GWM replacing fish meal protein and fed three times daily to triplicate groups of shrimp with an average initial weight of 1.73±0.003 g. In general, growth of the shrimp decreased with increasing level of GWM substitution. Except for the final weight (g) and weight gain (%), no significant differences was detected in specific growth rate (% day−1), daily feed intake (DFI), and feed conversion ratio (FCR) of GWM10 and the control diet. Replacing fish meal protein with 20–40 % GWM resulted in significantly poorer performance than the control diet. Survival rate was above 95 % in all treatments with no significant difference detected. The whole-body proximate composition of shrimp fed experimental diets was significantly affected by the inclusion of GWM with no definite trend. Interestingly, the GWM-based diets (GWM10, GWM20, GWM30, and GWM40) produced shrimp with more intense red/orange color and significantly higher total carotenoid concentration than the control diet.The present findings suggest that GWM is a good source of carotenoid and an acceptable alternative protein source for shrimp which can be included in the diet at a level of about 10 % without significant negative effect on survival, FCR, and SGR.